Legal Framework for Minimizing Electoral Barriers to Women's Representation in Indonesian Elections - Widjiastuti, Agustin; Kartiko, Nafis Dwi (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
This research aims to develop a legal framework that enhances the regulation of women's representation in politics and elections in Indonesia, employing a normative-dogmatic juridical method. The study assesses relevant legal principles and regulations, including the 1945 Constitution and the Election Law, through both statutory and conceptual approaches. The findings indicate that certain provisions, particularly Article 8, paragraph (2) of PKPU Number 10 of 2023, may diminish women's representation below the established minimum threshold, which contradicts constitutional mandates and superior legal frameworks. These results underscore the critical need for reforming electoral regulations to align with principles of gender equality and justice. The theoretical implications of this research contribute to a deeper understanding of how legal structures impact women's political participation, while the practical implications highlight the urgent necessity for revising electoral policies to effectively enhance women's representation. Furthermore, this study paves the way for future research to comparatively analyze the effectiveness of different electoral regulation models in promoting women's representation across diverse political contexts.